The age of migration international population movement in the modern world - Castles, Stephen; Miller, Mark J. (Palgrave MacMillan, 2009)
International migration is an ever-more central aspect of globalization in the contemporary world. The 4th edition of the leading text in the field has been completely recast and updated to provide a comprehensive assessment of the nature, extent and dimensions of international population movements and of their consequences